Retrofitting Sprawl : Addressing Seventy Years of Failed Urban Form - Talen, Emily, 1958- (Book collections on Project MUSE., 2015)
These twelve previously unpublished essays present innovative and practical ideas for addressing the harmful effects of sprawl. Sprawl is not only an ongoing focus of specialized magazines like Dwell; indeed, Time magazine has cited "recycling the suburbs" as the second of "Ten Ideas Changing the World Right Now." While most conversations on sprawl tend to focus on its restriction, this book presents an overview of current thinking on ways to fix, repair, and retrofit existing sprawl. Chapters by planners, geographers, designers, and architects present research grounded in diverse locales including Phoenix, Arizona; Seattle, Washington; Dublin, Ohio; and the Atlanta, Georgia, and Washington, D.C. metro areas. The authors address head-on the most controversial aspects of sprawl-issues of power and control, justice and equity, and American attitudes about regulating private development. But they also put these issues in practical contexts, bringing in examples of redesign that are already occurring around the country, including the retrofitting of corridors and the repurposing of cul-de-sacs. Whether fixing sprawl requires a "cultural shift" in thinking or a "coordinated effort" by local government, these essays testify that a combination of forethought and creative thinking will be needed. Contributors: Dave Amos, Aviva Hopkins Brown, Wesley Brown, David Dixon, Ellen Dunham-Jones, Aaron Golub, Nabil Kamel, Gerrit-Jan Knaap, Julia Koschinsky, Nico Larco, Rebecca Lewis, Gabriel Díaz Montemayor, Hector Navarro, Matthew Salenger, Brenda Case Scheer, Marc Schlossberg, Christian Solori, Benjamin W. Stanley, Galina Tachieva, Emily Talen, Whitney Warman, June Williamson, Milagros Zingoni.